2005
DOI: 10.1111/j.1749-6632.2005.tb00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acrylamide on Primary Neonatal Rat Astrocyte Functions

Abstract: The present study assessed biochemical endpoints indicative of acrylamide toxicity in astrocyte cultures derived from neonatal rat pups. Given earlier reports on the possible ability of acrylamide to induce astrocytomas in the Fischer 344 rat, we performed studies in neonatal rat astrocyte cultures from the Fischer 344 to assess the ability of acrylamide to induce astrocytic proliferation. Measurements on astrocytic proliferation included [3H]‐leucine incorporation, [3H]‐thymidine incorporation, and changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Thus, results from the MTT assays and Ki-67 expression using longer exposure times (>24 h) in the current study provide a better correlation between ACR treatments and proliferation inhibition. Aschner et al reported that ACR promoted astrocytic cell proliferation as seen by the increase in PCNA protein expression ; the inconsistency of those results with other studies may be due to the differences in exposure regimens and/or use of the cell types (rat primary astrocytic cells vs human astrocytoma cell lines). Therefore, the effects of ACR on cell proliferation between primary astrocytic cells and astrocytoma cells remain to be clarified.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Thus, results from the MTT assays and Ki-67 expression using longer exposure times (>24 h) in the current study provide a better correlation between ACR treatments and proliferation inhibition. Aschner et al reported that ACR promoted astrocytic cell proliferation as seen by the increase in PCNA protein expression ; the inconsistency of those results with other studies may be due to the differences in exposure regimens and/or use of the cell types (rat primary astrocytic cells vs human astrocytoma cell lines). Therefore, the effects of ACR on cell proliferation between primary astrocytic cells and astrocytoma cells remain to be clarified.…”
Section: Discussionmentioning
confidence: 88%
“…The results of the MTT assay and Ki-67 expression suggest that ACR exposure may inhibit the proliferation of astrocytoma cells during the active phases of the cell cycle. ACR-induced cell-growth suppression had been reported in many cell types (10,23,24,36,37); but the results for astrocytic cell have not been consistent (14)(15)(16)(17). As compared with proliferating cell nuclear antigen (PCNA), Ki-67 has been recognized as a more specific indicator for the proliferative activity of human glioblastomas (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASCT2 is more abundantly expressed in astrocytes than in neurons in culture [15,31]. A previous study from our laboratory has shown that exposure of astrocytes to acrylamide affects astrocytic glutamine uptake and expression of mRNA coding for Gln transporters [73] at concentrations comparable to those producing acute toxicity [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, acrylamide has been claimed to induce tumors at many organ sites in animals (16,29). It has also been reported that acrylamide promotes astrocytic cell proliferation and astrogliosis of astrocytic cells, which has been shown to be associated with brain tumors (2). Therefore, acrylamide-induced astrogliosis is worth further investigation.…”
Section: Discussionmentioning
confidence: 99%